Flood Risk in a Climate Change Context Exploring Current and Emerging Drivers - Miguel Ferreira, Tiago; Shi, Haiyun (IntechOpen, 2023)
Despite advancements in scientific knowledge and technological capabilities, flood disasters continue to escalate in severity and extent due to the combination of increasingly intensive land use and the growing effects of climate change. To combat this challenge, it is imperative to advance fundamental and applied research that enables targeted interventions, reduces vulnerability, enhances resilience, and supports decision-makers in implementing effective flood risk-reduction policies. This comprehensive volume contributes to this critical objective by collating recent studies and cutting-edge methodologies that delve into understanding both existing and emerging flood risk drivers within the current climate change context. From investigating the role of constructed wetlands in stormwater management and evaluating flood risk in historic urban areas to analysing the non-stationarity of extreme rainfall and advancing torrential rainfall forecasts, no aspect is left unexplored. Additionally, this volume delves into examining flood damage on agricultural land and understanding post-fire debris flow susceptibility. By meticulously investigating these multifaceted dimensions, the book arms readers with actionable insights and knowledge.The editors hope this comprehensive resource serves as a beacon for researchers, practitioners, and policymakers alike. By equipping readers with the latest advancements and methodologies, we hope this book empowers them to better comprehend flood risks, navigate the complexities of climate change, and forge a path toward a more resilient and sustainable future.